Sheep Nutrition 2002
DOI: 10.1079/9780851995953.0237
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition for sheep-meat production.

Abstract: The chapter elaborates on the factors that affect the efficiency of feed utilization by lambs, their body composition in terms of lean and fat content, and aspects of carcass quality including fat content and meat yield. Predictive mathematical models that would aid in making decisions in relation to nutritional management for sheepmeat production are presented. Aspects of growth and metabolism, the influence of genotype, and the effects of diet on composition of gain are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Based on these reports, it is evident that that nutrient demands, absorption and partitioning in ewes is different from those of wethers and results in the utilization of Spirulina for increasing liveweight and body conformation. Previous studies demonstrated that genetic variation between lambs influences nutrient partitioning and absorption despite the feeding of the same or identical rations Lewis et al, 2006;Oddy and Sainz, 2002;Cake et al, 2007;Wynn and Thwaites, 1981). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these reports, it is evident that that nutrient demands, absorption and partitioning in ewes is different from those of wethers and results in the utilization of Spirulina for increasing liveweight and body conformation. Previous studies demonstrated that genetic variation between lambs influences nutrient partitioning and absorption despite the feeding of the same or identical rations Lewis et al, 2006;Oddy and Sainz, 2002;Cake et al, 2007;Wynn and Thwaites, 1981). …”
Section: Discussionmentioning
confidence: 99%
“…However, the insignificant influence of Spirulina level on ADG, CG and WH in the current study suggests that the physiological mechanisms involved are not fully understood at the moment. Thus, clarification of nutrient partitioning into different tissues including muscle, adipose and wool would allow greater insight into the underlying mechanisms in this species since lamb productivity is a function of genetic and environmental interactions (Black, 1983;Oddy and Sainz, 2002). Thus, prime lamb productivity depends on not only environmental factors such as feed ration quality and quantity, but also on genetic factors in terms of lamb sire breed and sex (Malau-Aduli et al, 2009c;Sobrinho et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate a sheep for meat production potential, growth performance is an important character which determines the overall productivity of the flock and the economic return from sheep production enterprise. Although heredity dictates the maximum amount of growth and development, nutrition along with other environmental factors govern the actual rate of growth and extent to which development is attained [10] [11]. Nevertheless any additional input than required for normal physiological needs may not induce growth beyond the genetic potential of the animal [12].…”
Section: Growth Responsementioning
confidence: 99%
“…Various research results noted that animal growth is a function of the animal's genetic potential and the extent to which the environment, particularly nutrition, allows this potential to be expressed [10] [11]. Effect of genotype [12] [13], genotype and feeding system [14], and genotype and levels of feeding [15] on performance of sheep has been reported, although potential differences in response to different feed levels among genotypes have not been sufficiently illustrated.…”
Section: Introductionmentioning
confidence: 99%